KAJIAN KRIMINOLOGI TERHADAP KEJAHATAN BEGAL DI KOTA SAMARINDA - Dina Paramitha Hefni Putri, Muhammad Laksamana dan (Universitas 17 Agustus 1945 Samarinda, 2020)
Begal motor action in the city of Samarinda increasingly disturbing the public, they acted not knowing the time and place. The intensity has also increased sharply. However, there has been no preventive efforts by the police on a large scale to ensure that Samarinda is free from the